Desenvolvimento e avaliação de oficinas culinárias a partir do uso integral dos alimentos em um CAPS AD - COSTA, Barbara Liliane Cardoso (2023)
Introduction: Integral Utilization of Food promotes easy access to food, makes preparation low cost and improves nutritional value, as well as assisting with the reduction of organic waste disposed in the environment and food waste. Culinary workshops focusing on the integral use of food are among the therapeutic activities that can be performed at the Psychosocial Alcohol Drugs Centers (CAPS AD) and that help in the treatment of users of psychoactive substances through the practice and awareness of the integral use of food. foods. Objective: To develop and evaluate culinary workshops from the integral use of food in a CAPS AD of Belém- PA. Material and Methods: Descriptive, exploratory and quantitative and qualitative study conducted between June and October / 2019 through the application of a semi structured form that allowed the identification of the public's knowledge about the full use of food, in addition to the application of a food test. acceptability concerning preparations prepared during culinary workshops. Results: 23 users participated in the survey, in which a total of 65.2% of respondents reported not having heard and not knowing if they have heard about full use of food. Regarding the acceptability of the preparations, the result was positive for all evaluations performed. Conclusion: It was possible to identify the lack of knowledge about the integral use of food by most users, indicating the need to address the theme through educational activities.